IDENTIFIKASI KEANEKARAGAMAN DAN POLA SEBARAN BURUNG YANG TERDAPAT DI KAWASAN JALUR PENDAKIAN KAWAH RATU TAMAN NASIONAL GUNUNG HALIMUN SALAK, CIDAHU, SUKABUMI - Novira, Rahmi; Uki Sajiman, Supardi; Indar Praditya, Dimas; Dwi Kurnia, Tika (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
Birds are one of the biological assets owned in Indonesia. The existence of feed, nesting places and layouts are factors that influence bird species richness at the local level. This study aims to determine the types, populations and distribution of birds found in the Crater of Queen TNGHS Climbing Trail, Cidahu, Sukabumi. This observation uses a fixed distance "Point Count" method. This method is done by seeing or hearing each bird species found at the fixed point of calculation. The observations showed that there were 12 bird species, of which 9 bird species found in the Queen's Crater Gorge, Cidahu Ascent Pathway Area, Sukabumi showed a uniform spreading pattern, and 3 bird species showed a clustered distribution pattern with the dominant species of Swallow Bird.